2021
DOI: 10.1016/j.psj.2021.101085
|View full text |Cite
|
Sign up to set email alerts
|

SC75741 antagonizes vesicular stomatitis virus, duck Tembusu virus, and duck plague virus infection in duck cells through promoting innate immune responses

Abstract: Duck Tembusu virus ( DTMUV ) and duck plague virus ( DPV ) are typical DNA and RNA viruses of waterfowl, causing drastic economic losses to the duck farm industry in terms of high mortality and decreased egg production. These 2 viruses reappear from time to time because the available vaccines fail to provide complete immunity and no clinical antiviral drugs are available for them. In the present study, we evaluated the antiviral activity of SC75741 for DTMUV, DPV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Further, we also found HSP90AB1 knockout resulted in the upregulation of NFKBIA caused by PDCoV infection was enhanced and led to a reduction of NFKBIA, NFKBIB and NKAP mRNA levels ( Figure 9 ), indicating that the effect of HSP90AB1 on PDCoV infection might be related to the NF-κB signaling pathway. Previous research has also reported that the NF-κB signaling pathway might be a suitable target for antiviral intervention, and inhibition of this signaling pathway by suppressing NF-κB activity might result in a reduction in virus infection [ 54 ]. In our study, the NF-κB inhibitors, JSH-23, SC75741 and QNZ, reduced PDCoV infection at the mRNA and protein levels ( Figure 10 ), similar to previous results obtained for some other viruses, such as avian influenza A viruses (IAVs) [ 55 ], severe fever with thrombocytopenia syndrome virus (SFTSV) and heartland virus (HRTV) [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, we also found HSP90AB1 knockout resulted in the upregulation of NFKBIA caused by PDCoV infection was enhanced and led to a reduction of NFKBIA, NFKBIB and NKAP mRNA levels ( Figure 9 ), indicating that the effect of HSP90AB1 on PDCoV infection might be related to the NF-κB signaling pathway. Previous research has also reported that the NF-κB signaling pathway might be a suitable target for antiviral intervention, and inhibition of this signaling pathway by suppressing NF-κB activity might result in a reduction in virus infection [ 54 ]. In our study, the NF-κB inhibitors, JSH-23, SC75741 and QNZ, reduced PDCoV infection at the mRNA and protein levels ( Figure 10 ), similar to previous results obtained for some other viruses, such as avian influenza A viruses (IAVs) [ 55 ], severe fever with thrombocytopenia syndrome virus (SFTSV) and heartland virus (HRTV) [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The viral genome copy number was quantified using an absolute quantitative PCR ( Q-PCR ). The quantitative primers for the detection of DPV UL30 gene were previously designed in our laboratory ( Tian et al, 2021 ), DPV UL30-F: TTTCCTCCTCCTCGCTGAGTG, and DPV UL30-R: CCAGAAACATACTGTGAGAGT. The PCR amplification conditions are as follows: 95°C for 30 s, followed by 40 cycles at 95°C for 5 s and 60°C for 30 s. Then, the PCR products were determined by the standard curve previously established in the laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…All RNA samples’ purity was detected by analyzing the A260/A280 ration using a Nano drop ND-1000spectrophotometer (Nano drop Technologies), which was expected to be 1.8~2.0. Total RNAs were reverse transcribed into cDNA with the ReverTra Ace qPCR RT Kit (Toyobo, Osaka, Japan); RT-qPCR was performed primarily according to a previous method ( 21 ). Target genes were detected using the previously described primers.…”
Section: Methodsmentioning
confidence: 99%